Three-Dimensional Thermal-Stress Analysis of Semi-infinite Transversely Isotropic Composites - Tokovyy, Yuriy; Boiko, Dmytro; Gao, Cunfa (Transactions of Nanjing University of Aeronautics & Astronautics, 2021)
By making use of the direct integration method,an exact analysis of the general three-dimensional thermoelasticity problem is performed for the case of a transversely isotropic homogeneous half-space subject to local thermal and force loadings. The material plane of isotropy is assumed to be parallel to the limiting surface of the halfspace. By reducing the original thermoelasticity equations to the governing ones for individual stress-tensor components,the effect of material anisotropy in the stress field is analyzed with regard to the feasibility requirement,i.e.,the finiteness of the stress field at a distance from the disturbed area. As a result,the solution is constructed in the form of explicit analytical dependencies on the force and thermal loadings for various kinds of transversely isotropic materials and agrees with the basic principles of the continua mechanics. The solution can be efficiently used as a benchmark one for the direct computation of temperature and thermal stresses in transversely isotropic semi-infinite domains,as well as for the verification of solutions constructed by different means.